Reversible C-H bond silylation with a neutral silicon Lewis acid - Thorwart, Thaddäus; Greb, Lutz (Chemical science, 2023)
The silicon-carbon bond is a valuable linchpin for synthetic transformations. However, installing Si-C functionalities requires metalated C-nucleophiles, activated silicon reagents (silylium ions, silyl radicals, and silyl anions), or transition metal catalysis, and it occurs irreversibly. In contrast, spontaneous C-H silylations with neutral silanes leading to anionic silicates, and their reversible deconstruction, are elusive. Herein, the CH-bond silylation of heterocycles or a terminal alkyne is achieved by reaction with bis(perfluoro(N-phenyl-ortho-amidophenolato))silane and 1,2,2,6,6-pentamethylpiperidine. Computational and experimental insights reveal a frustrated Lewis pair (FLP) mechanism. Adding a silaphilic donor to the ammonium silicate products induces the reformation of the C-H bond, thus complementing previously known irreversible C-H bond silylation protocols. Interestingly, the FLP “activated” N-methylpyrrole exhibits “deactivated” features against electrophiles, while a catalytic functionalization is found to be effective only in the absence of a base.
Veröffentlicht: 14. September 2023
Gesehen am 20.11.2023